2002
DOI: 10.1053/jhep.2002.33162
|View full text |Cite
|
Sign up to set email alerts
|

Role of CCR2 in macrophage migration into the liver during acetaminophen-induced hepatotoxicity in the mouse

Abstract: The biological effects of monocyte chemoattractant protein (MCP) 1 are mediated by binding to C-C chemokine receptor (CCR) 2. In the present studies, we used CCR2 knockout (CCR2؊/؊) mice to examine the role of MCP-1 in acetaminophen-induced macrophage accumulation in the liver, expression of inflammatory cytokines, and hepatotoxicity. We found that hepatic expression of CCR2 and MCP-1 was increased 10-fold and 20-fold, respectively, 12 to 72 hours after administration of acetaminophen to wild-type mice. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
208
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(225 citation statements)
references
References 43 publications
17
208
0
Order By: Relevance
“…The origin of hepatic CCL2 in acute liver injury is known to be both resident Kupffer cells and injured hepatocytes leading to the recruitment of monocytes/macrophages, NK cells, T cells and neutrophil granulocytes. 27 Moreover, hepatic-derived CCL2 is able to stimulate the expansion, mobilization and subsequent trafficking of bone marrow population of activated CD11b + F4/80 + monocytes/macrophages to the liver, accounting for the marked expansion in hepatic macrophage numbers seen after acute liver injury. 28 Pro-inflammatory, M1-polarized macrophages can contribute to the recruitment of additional inflammatory and other immune cells into the tissue, while M2-polarized macrophages are predominantly anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of hepatic CCL2 in acute liver injury is known to be both resident Kupffer cells and injured hepatocytes leading to the recruitment of monocytes/macrophages, NK cells, T cells and neutrophil granulocytes. 27 Moreover, hepatic-derived CCL2 is able to stimulate the expansion, mobilization and subsequent trafficking of bone marrow population of activated CD11b + F4/80 + monocytes/macrophages to the liver, accounting for the marked expansion in hepatic macrophage numbers seen after acute liver injury. 28 Pro-inflammatory, M1-polarized macrophages can contribute to the recruitment of additional inflammatory and other immune cells into the tissue, while M2-polarized macrophages are predominantly anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated whether MCP-1 is responsible for the production of mid-and latephase cytokines IL-8 and IL-6, respectively, induced by SEA stimulation of IMFs. The biological effects of MCP-1 are mostly mediated by binding to the CC chemokine receptor CCR-2 (49,50). Therefore, to understand the responsiveness of IMFs to MCP-1, we analyzed the surface expression of CCR-2 by flow cytometry on IMFs.…”
Section: Mcp-1 Is Responsible For Il-8 and Il-6 Production Induced Bymentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The inflammatory mediators such as cytokines, chemokines, reactive oxygen, and nitrogen species released by Kupffer cells/macrophages have been implicated in APAP hepatotoxicity. [5][6][7][8][9][10] We have previously reported that natural killer (NK) and NKT cells, a major component of liver innate immune system, play a critical role in the severity and progression of APAP-induced liver injury by secreting cytokine interferon gamma (IFN-␥), modulating chemokine production and recruitment of inflammatory cells into the liver. 11 Our previous study also identified neutrophils as a major fraction of inflammatory cells in the liver from APAP-challenged mice.…”
mentioning
confidence: 99%